Comparative Genomics of Mycoplasma bovis Strains Reveals That Decreased Virulence with Increasing Passages Might Correlate with Potential Virulence-Related Factors - Rasheed, Muhammad A.; Qi, Jingjing; Zhu, Xifang; Chenfei, He; Menghwar, Harish; Khan, Farhan A.; Zhao, Gang; Zubair, Muhammad; Hu, Changmin; Chen, Yingyu; Chen, Huanchun; Guo, Aizhen (Frontiers in Cellular and Infection Microbiology, 2017)
Mycoplasma bovis is an important cause of bovine respiratory disease worldwide. To understand its virulence mechanisms, we sequenced three attenuated M. bovis strains, P115, P150, and P180, which were passaged in vitro 115, 150, and 180 times, respectively, and exhibited progressively decreasing virulence. Comparative genomics was performed among the wild-type M. bovis HB0801 (P1) strain and the P115, P150, and P180 strains, and one 14.2-kb deleted region covering 14 genes was detected in the passaged strains. Additionally, 46 non-sense single-nucleotide polymorphisms and indels were detected, which confirmed that more passages result in more mutations. A subsequent collective bioinformatics analysis of paralogs, metabolic pathways, protein-protein interactions, secretory proteins, functionally conserved domains, and virulence-related factors identified 11 genes that likely contributed to the increased attenuation in the passaged strains. These genes encode ascorbate-specific phosphotransferase system enzyme IIB and IIA components, enolase, L-lactate dehydrogenase, pyruvate kinase, glycerol, and multiple sugar ATP-binding cassette transporters, ATP binding proteins, NADH dehydrogenase, phosphate acetyltransferase, transketolase, and a variable surface protein. Fifteen genes were shown to be enriched in 15 metabolic pathways, and they included the aforementioned genes encoding pyruvate kinase, transketolase, enolase, and L-lactate dehydrogenase. Hydrogen peroxide (H2O2) production in M. bovis strains representing seven passages from P1 to P180 decreased progressively with increasing numbers of passages and increased attenuation. However, eight mutants specific to eight individual genes within the 14.2-kb deleted region did not exhibit altered H2O2 production. These results enrich the M. bovis genomics database, and they increase our understanding of the mechanisms underlying M. bovis virulence.